The Masturbator and the Ban - Kök, Murat Mümtaz (Conatus - Journal of Philosophy, 2020)
In this paper, I will expand upon Giorgio Agamben’s argument in his defining work Homo Sacer where he accused Immanuel Kant for introducing the state of exception to modernity. According to Agamben, Kant managed to do this by introducing the form of law as “being in force without signifying.” In this line, I will argue that ‘the ban’ is indeed inherent within Kantian morality and all subjects under the law stand in “pure relation of abandonment” vis-a-vis the law. In order to show this, I will focus on Kant’s views on masturbation in the context of his disdainful views about the body and sex and how through these views he formulated ‘duties to oneself’ in a way that condemns the masturbator to ‘bare life.’